2016
DOI: 10.1021/acs.jafc.6b01512
|View full text |Cite
|
Sign up to set email alerts
|

Specific Synergist for Neonicotinoid Insecticides: IPPA08, a cis-Neonicotinoid Compound with a Unique Oxabridged Substructure

Abstract: Insecticide synergists are key components to increase the control efficacy and reduce active ingredient use. Here, we describe a novel insecticide synergist with activity specific for insecticidal neonicotinoids. The synergist IPPA08, a cis configuration neonicotinoid compound with a unique oxabridged substructure, could increase the toxicity of most neonicotinoid insecticides belonging to the Insecticide Resistance Action Committee (IRAC) 4A subgroup against a range of insect species, although IPPA08 itself w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 36 publications
1
29
0
1
Order By: Relevance
“…Many synergists exhibit synergistic effects on the toxicity of insecticides, and the synergistic mechanism of most synergists is through inhibiting the detoxification eznymes activities, such as PBO inhibiting P450 monooxygenases activities, TPP inhibiting ESTs activities, and DEM inhibiting GSTs activities (Bao et al, 2016). To find out whether DDBAC showed inhibition effects on the activities of detoxification enzymes, DDBAC was applied to insects and then the changes in enzyme activities were determined.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many synergists exhibit synergistic effects on the toxicity of insecticides, and the synergistic mechanism of most synergists is through inhibiting the detoxification eznymes activities, such as PBO inhibiting P450 monooxygenases activities, TPP inhibiting ESTs activities, and DEM inhibiting GSTs activities (Bao et al, 2016). To find out whether DDBAC showed inhibition effects on the activities of detoxification enzymes, DDBAC was applied to insects and then the changes in enzyme activities were determined.…”
Section: Resultsmentioning
confidence: 99%
“…Reducing pesticide application, increasing unit activity and selectivity, and reducing pesticide resistance development rate are important ways to deal with this dilemma. And the application of synergists is an effective strategy to increase pesticides toxicity and reduce pesticides usage amount (Bao et al, 2016). Here, we found that DDBAC, a cationic adjuvant, showed significant enhancement effect on chlorpyrifos, although DDBAC itself was inactive against insect pests at these synergistic concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the case for IPPA08, an eight-membered homolog of the cis-neonicotinoid cycloxaprid that can be used as neonicotinoid-specific synergist (Bao et al 2016). However, IPPA08 increases the toxicity of several neonicotinoid insecticides (i.e., acetamiprid, thiacloprid, clothianidin, and imidacloprid) to nontarget species as well, such as honeybees and the brown planthopper (Nilaparvata lugens) (Bao et al 2016).…”
Section: Synergymentioning
confidence: 99%
“…This is the case for IPPA08, an eight-membered homolog of the cis-neonicotinoid cycloxaprid that can be used as neonicotinoid-specific synergist (Bao et al 2016). However, IPPA08 increases the toxicity of several neonicotinoid insecticides (i.e., acetamiprid, thiacloprid, clothianidin, and imidacloprid) to nontarget species as well, such as honeybees and the brown planthopper (Nilaparvata lugens) (Bao et al 2016). Also, the root fertilizer BRoot Feed^(i.e., 9% N, 7% Ca, 1.5% Mg, and 0.1% B) subirrigated in the growing medium has been able to enhance imidacloprid efficacy against the whitefly on tomato (Sun and Liu 2016).…”
Section: Synergymentioning
confidence: 99%